Strengthening Exercises In Management Of Shoulder Pain In Diabetic Population (Journal of Pharmaceutical Negative Results, 2022)
Shoulder pain is a common complaint of diabetic patients that causes motion limitations and functional disability. Adhesive capsulitis (AC) is the most common disabling shoulder disorder. There is no optimal non-surgical treatment for managing AC in patients with diabetes.we are not sure what is the best treatment to manage Frozen Shoulder in patients with diabetes. We donot know how diabetes can affect recovery after shoulder replacement surgery. Also, we arenot sure what factors can affect function after shoulder replacement surgery.Weakness of the shoulder rotator muscles is associated with shoulder pain.Purpose: The aim of this study was to describe and evaluate a physiotherapy program targeted to reduce pain intensity and improve the daily functioning of diabetics with shoulder problems. It was hypothesized that patients receiving specific physiotherapy treatment improved more frequently and rapidly than diabetic patients followed up without specific physiotherapeutic intervention. Method: A pre-post treatment design was completed for a group of 10 subjects. The treatment protocol, also applied during the daily activities of the subjects, was aiming at reducing pain intensity and shoulder stiffness and improving impaired functioning in daily activities by muscle relaxation, light-load exercise and enhancing the co-ordination.